Comparative study of RC and steel-concrete composite buildings by seismic fragility approach - Desai, R.M.; Tande, S.N. (Journal of Structural Engineering, 2024)
The present paper aims to prove the effectiveness of steel-concrete composite building over conventional RC building when subjected to seismic load. The steel-encased sections of the composite building are designed as per the criteria prescribed in the Eurocode EN 1994. The seismic performance of the composite building and the RC building is estimated through the analytical fragility function. Further, the pushover analysis is performed by assigning the user-defined hinges to frame the elements of the composite and RC buildings. The pushover-based fragility curves are developed for the various damage states. The median capacity and standard deviation for the different damage states of fragility curves are estimated by using the previous literature. Finally, it is proved that with the inclusion of the steel-encased profiles in the building, the seismic performance of steel-concrete composite building has increased in terms of strength, stiffness, ductility and damage pattern compared to conventional building.